Mounds in Oxia Planum: The Burial and Exhumation of the ExoMars Rover Landing Site. Issue 11 (12th November 2022) - McNeil, Joseph D.; Fawdon, Peter; Balme, Matthew R.; Coe, Angela L.; Thomas, Nicolas
Abstract: Oxia Planum, the planned landing site of the ExoMars " Rosalind Franklin " rover, is a low relief clay‐bearing plain, of which approximately 1% is covered by 396 upstanding isolated landforms ("mounds"). The mounds are continuous with a circum‐Chryse mound population representing the remnants of a regionally significant Noachian‐aged deposit. This detailed study suggests that the Oxia Planum mounds are also erosional remnants of this deposit, with little evidence to suggest they are constructional landforms such as sedimentary volcanoes. We calculate that up to 130 m of mound‐forming material has been removed from the landing site through erosion. The mound‐forming layer lies unconformably on the clay‐bearing plains with the upper surface severely truncated by significant erosion resulting in the topography we see today. The mounds themselves comprise at least three members, distinct in color and texture, separated stratigraphically by further unconformities. Calculated minimum erosion/deposition rates of the removed mound material are comparable to previous Noachian estimates, suggesting a more erosive (and probably therefore warmer and/or wetter) environment than today. The clay‐bearing materials which remain buried directly under the mounds have been continually protected from the Martian environment since the Noachian, and are likely to represent some of the most pristine clay‐rich materials in the landing site. By inference, the plains directly adjacent to the mounds are most likely to have been exposed for less time than areas further from the mounds. These are therefore amongst the most likely locations where Rosalind Franklin could sample recently exposed materials and hence detect biosignatures. Plain Language Summary: The Oxia Planum region of Mars is the landing site of ESA's ExoMars " Rosalind Franklin " rover, which will search for evidence of past life in the ancient rocks of the area. In the landing site there are hundreds of sub‐kilometer‐scale "mounds" that are likely to have been part of an extensive layer which covered the region in the distant past. To understand more about the mounds, we examined their geological features, calculated the volume of eroded material, and observed their relationships to other important features within the landing site. We find: (a) On average, the layer was up to 70% thinner in Oxia Planum than elsewhere in the region. (b) There are gaps in the geological record below, within, and above the mounds indicating periods of erosion. (c) The layer was eroded at a much faster rate in the past than in the present, consistent with a warmer and wetter ancient Martian environment. Areas around the mounds were probably exposed relatively recently, and are therefore likely to have been protected from the harsh Martian environment for longer than other areas. Consequently, these areas may be amongst the best places for the rover to search for evidence of past life. Key Points: Mounds in Oxia Planum represent eroded remnants of a circum‐Chryse deposit that was up to 130 m thick in the ExoMars rover landing site The mounds unconformably overlie the clay‐bearing unit (CBU) and are in turn unconformably onlapped by the dark resistant unit The plains immediately adjacent to the mounds are the most recently exposed parts of the astrobiologically important CBU